THEORETICAL AND METHODOLOGICAL ASPECTS OF OVERCOMING TYPES OF DYSLEXIA IN PRIMARY SCHOOL CHILDREN (Multidisciplinary Journal of Science and Technology, 2025)
AbstractThis article examines the types of dyslexia observed in primary school children and analyzes the theoretical and methodological foundations for overcoming them. Dyslexia is one of the urgent issues in modern pedagogy and special education, as its timely identification and effective organization of correctional work have a positive impact on the learning process of pupils. The study highlights phonemic, optical, semantic, and other forms of dyslexia, as well as provides a scientific analysis of theoretical and methodological approaches applied to its remediation.